Effects of Happiness Levels in Asia - Rully Firmansyah; Dyah Wulansari (Jurnal Ekonomi Pembangunan, 2020)
Happiness is the main goal in life. To measure someone's happiness is not easy, many opinions have emerged. Some say happiness can be measured through the satisfaction of one's life, some say happiness is measured through one's income, education, and health. The number of people's opinions to measure one's happiness appears as an indicator of happiness. At present, there are 48 indicators. One of the most accurate is HPI. The HPI indicator is very important for a country to increase the happiness of its people. Example: life expectancy in a country will increase and unemployment will decrease because a person has extensive knowledge and knowledge that is needed both by himself and the company that will accept him as his employee. The purpose of this study is to find out how HDI influences, life expectancy, unemployment on the level of happiness of people in ASIA. In this study using secondary data sources conducted by taking HDI data, life expectancy, unemployment in ASIA, and HPI data on ASIA. The results of the analysis using quantitative methods indicate that the independent variables namely HDI, life expectancy, and unemployment. Has a significant positive effect on the HPI dependent variable.